Plagas y enfermedades de carácter cuarentenario en flores de corte - Cárdenas, Jaime; Forero, Álvaro; Forero, Dimitri; Lee, Rebecca; Londoño, Martha; Rojas, José Pablo; Arévalo, Emilio (ICA, 2018)
Flores y ornamentales